THE EFFECT OF MARKETING MIX ON CONSUMER DECISIONS PT. NUGRAHA EAKURIR (JNE) LINE, MANNA BRANCH, SELATAN BENGKULU REGENCY - Popi Herawati; Siswanto; Andriyani Prawitasari (Penerbit Jurnal Indonesia, 2020)
This study aims to analyze the influence of the marketing mix on consumer decisions at PT. JNE (Jalan Nugraha Ekakurir) Manna Bengkulu Selatan branch. The data of this study were obtained from a questionnaire (questionnaire) and several observations. The population in this study were 1500 people and a sample of 150 people who used the delivery service of PT. JNE Manna Bengkulu Selatan branch. The type of research used, the sampling of data management techniques used is a simple linear regression test and hypothesis testing (R test and t test). The results of the analysis show that the constant is 82.563; it means that if the marketing mix (X) value is 0, then the consumer decision (Y') value is 82.563. The regression coefficient of the marketing mix variable (X) is 0.303; meaning that if the value of the marketing mix is ​​1, then the consumer's decision (Y') will increase by 0.303. A positive coefficient means that there is a positive relationship between the marketing mix and consumer decisions. Partially, product policies, distribution policies, and promotion policies affect consumer decision making. The distribution policy variable is the dominant variable influencing consumer decision making.